DEFINING FRIENDSHIP THROUGH THE FILM ALADDIN (2019) - Dwita Oktaviani Sinabutar2; Three Debora E. Tampubolon; Lesly Yunus; Mariana Siregar; Rudy Rudy (English Language Teaching Prima Journal (ELT), 2021)
Abstract As one of the important things in human life, friendship is an essential discussion because it is experienced by almost all people. Moreover, the portrait of friendship has been frequently shown in films. Therefore, this study aims to identify how friendship is depicted in the film Aladdin (2019) and to analyze the significance of friendship for people. It is expected that this study can contribute in the form of theory development in social and cultural studies and help people understand the value of friendship. The picture of friendship that appears in the film in the form of dialogs was used as the main data to be analyzed in this study. By applying representation theory as a semiotic approach, film dialogs were treated as symbols that could be interpreted. The result of analysis reveals that the representation of friendship in the Aladdin can be seen through the three main concepts – the sense of care, mutuality and solidarity which are considered significant in friendship. Furthermore, the result also reveals that everyone can interpret friendship based on their experience. This also affects the purpose of friendship. Keywords: friendship, representation of friendship, care, mutuality, solidarity